2022
DOI: 10.1186/s12957-022-02646-7
|View full text |Cite
|
Sign up to set email alerts
|

The role of interleukin‑7 serum level as biological marker in breast cancer: a cross‑sectional, observational, and analytical study

Abstract: Background The important role that the immune system plays in malignant diseases is well known. The action of interleukin-7 (IL-7) as a cytokine has been observed in many cellular processes, both in normal cells of the immune system and in some cancer cells. The aim of this study has been to explore whether there is any elevation of interleukin-7 serum levels in early invasive breast cancer (EIBC) patients in comparison with healthy controls. In addition, the correlation between the IL-7 serum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…In a study conducted on 213 BC patients, researchers discovered that EBC patients had significantly higher IL-7 serum levels than healthy control cases (p < 0.001). IL-7 serum levels, on the other hand, have not been linked to tumor size, lymph node metastasis, or tumor progression regardless of age or menopausal status of the patients [12] -8-Iso-prostaglandin F2α (8-iso-PGF2α): Increased lipid peroxidation and the absence of antioxidants, combined with oxidative stress, have been related to breast tumorigenesis in BC studies [26,27]. Lipid peroxidation is the most well researched free radical-inducing process linked to cancer, assisting in the creation of numerous relatively stable breakdown products, such as isoprostanes, which serve as indirect cellular prooxidant indicators in bodily fluids [28][29][30][31].…”
Section: Resultsmentioning
confidence: 97%
“…In a study conducted on 213 BC patients, researchers discovered that EBC patients had significantly higher IL-7 serum levels than healthy control cases (p < 0.001). IL-7 serum levels, on the other hand, have not been linked to tumor size, lymph node metastasis, or tumor progression regardless of age or menopausal status of the patients [12] -8-Iso-prostaglandin F2α (8-iso-PGF2α): Increased lipid peroxidation and the absence of antioxidants, combined with oxidative stress, have been related to breast tumorigenesis in BC studies [26,27]. Lipid peroxidation is the most well researched free radical-inducing process linked to cancer, assisting in the creation of numerous relatively stable breakdown products, such as isoprostanes, which serve as indirect cellular prooxidant indicators in bodily fluids [28][29][30][31].…”
Section: Resultsmentioning
confidence: 97%
“…Similarly, an IL‐7 variant (IL‐7δ5) has pivotal roles in AKT‐mediated cell proliferation, apoptosis, angiogenesis, and metastasis in breast cancer, 60 all of which may increase tumor size. However, a recent (2022) observational study in breast cancer found no significant correlation between tumor size and IL‐7 serum concentrations, 61 thus the effect of IL‐7 may depend on the type of tumor or could be limited to the tumor microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…[123,124] that may result from an intensive secretion of IL-7 by the tumor as IL-7 facilitates B-cell maturation. [125,126] Plasma cells mediate Ab-dependent cytotoxicity, Abdependent cellular phagocytosis, and complement-dependent cytotoxicity. [127] The antibodies secreted by plasma cells are categorized into different classes, with immunoglobulin G (IgG) antibodies providing the major antitumor cytotoxicity.…”
Section: Circulating B-cells In Breast Cancermentioning
confidence: 99%
“…[ 123,124 ] that may result from an intensive secretion of IL‐7 by the tumor as IL‐7 facilitates B‐cell maturation. [ 125,126 ]…”
Section: Adaptive Immune Cells In the Pathogenesis Of Breast Cancermentioning
confidence: 99%